14.1k views
2 votes
A mass m1 hangs from a spring k and is in static equilibrium. A second mass m2 drops through a height h and sticks to m1 without rebound. Determine the subsequent motion u(t) measured from the static equilibrium position of m1 and k.

User Cosmas
by
6.0k points

1 Answer

5 votes

Answer:


\mathbf{u(t) =(m_2g )/(k)(1 - cos \omega_n t) + (√(2gh))/(\omega_n)* (m_1)/(m_1+m_2)sin \omega _n t}

Step-by-step explanation:

From the information given:

The equation of the motion can be represented as:


(m_1 +m_2) \hat u + ku = m_2 g--- (1)

where:


m_1 = mass of the body 1


m_2 = mass of the body 2


\hat u = acceleration

k = spring constant

u = displacement

g = acceleration due to gravity

Recall that the formula for natural frequency
\omega _n = \sqrt{(k)/(m_1+m_2)}

And the equation for the general solution can be represented as:


u(t) = A cos \omega_nt + B sin \omega _n + (m_2g)/(k) --- (2)

To determine the initial velocity, we have:


\hat u_2^2 = 2gh


\hat u_2 = √(2gh)

where h = height

Suppose we differentiate equation (2) with respect to time t; we have the following illustration:


\hat u (t) = - \omega_n A sin \omega_n t+ \omega_n B cos \omega _n t + 0

now if t = 0

Then


\hat u (0) = - \omega_n A sin \omega_n (0)+ \omega_n B cos \omega _n (0) + 0


= \omega _n B

Using the law of conservation of momentum on the impact;


m_2 \hat u_2=(m_1+m_2) \hat u (0)

By replacing the value of
\hat u_2 with
\sqrt{2gh

Then the above equation becomes:


m_2 * √(2gh)=(m_1+m_2) \ u(0)

Making u(0) the subject of the formula, we have:


u(0)= ( m_2 * √(2gh))/((m_1+m_2))

Similarly, the value of the variable can be determined as follows;

Using boundary conditions


0 = A cos 0 + B sin 0 + (m_2g)/(k)


0 = A (1)+0+ (m_2g)/(k)


A =- (m_2g)/(k)

Also, if
\hat u (0) = \omega_nB

Then :


(m_2)/(m_1+m_2)√(2gh) = \omega_n B

making B the subject; we have:


B = (m_2)/(m_1 + m_2)(√(2gh))/(\omega_n)

Finally, replacing the value of A and B back to the general solution at equation (2); we have the equation of the subsequent motion u(t) which is:


\mathbf{u(t) =(m_2g )/(k)(1 - cos \omega_n t) + (√(2gh))/(\omega_n)* (m_1)/(m_1+m_2)sin \omega _n t}

User Rushy Panchal
by
5.3k points